The Gene Expression Profile of Uropathogenic Escherichia coli in Women with Uncomplicated Urinary Tract Infections Is Recapitulated in the Mouse Model - Arwen E. Frick-Cheng (American Society for Microbiology, 2020)
ABSTRACT Uropathogenic Escherichia coli (UPEC) is the primary causative agent of uncomplicated urinary tract infections (UTIs). UPEC fitness and virulence determinants have been evaluated in a variety of laboratory settings, including a well-established mouse model of UTI. However, the extent to which bacterial physiologies differ between experimental models and human infections remains largely understudied. To address this important issue, we compared the transcriptomes of three different UPEC isolates in human infection and under a variety of laboratory conditions, including LB culture, filter-sterilized urine culture, and the UTI mouse model. We observed high correlation in gene expression between the mouse model and human infection in all three strains examined (Pearson correlation coefficients of 0.86 to 0.87). Only 175 of 3,266 (5.4%) genes shared by all three strains had significantly different expression levels, with the majority of them (145 genes) downregulated in patients. Importantly, gene expression levels of both canonical virulence factors and metabolic machinery were highly similar between the mouse model and human infection, while the in vitro conditions displayed more substantial differences. Interestingly, comparison of gene expression between the mouse model and human infection hinted at differences in bladder oxygenation as well as nutrient composition. In summary, our work strongly validates the continued use of this mouse model for the study of the pathogenesis of human UTI. IMPORTANCE Different experimental models have been used to study UPEC pathogenesis, including in vitro cultures in different media, tissue culture, and mouse models of infection. The last is especially important since it allows evaluation of mechanisms of pathogenesis and potential therapeutic strategies against UPEC. Bacterial physiology is greatly shaped by environment, and it is therefore critical to understand how closely bacterial physiology in any experimental model relates to human infection. In this study, we found strong correlation in bacterial gene expression between the mouse model and human UTI using identical strains, suggesting that the mouse model accurately mimics human infection, definitively supporting its continued use in UTI research.